Rola partii i ugrupowań politycznych w wydarzeniach „tulipanowej rewolucji” w Kirgistanie - Schukuralieva, Nartsiss (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
The activization of political parties, stimulated both by the authorities and opposition, and the use of ‘new’ methods that had not been used before, were an inseparable element of the events of the so-called ‘Tulip Revolution’. This time, the political games of the salon were supplemented by the activity aimed at establishing connections with the electorate. The establishment of youth organizations, working with people and active presence in the media and the Internet became an element of political practice. The ultimate success of the opposition parties was that they broke political apathy and stimulated the belief that changes can be achieved via the (passive or active) involvement of the entire community in political events. Yet this was virtually the only success which turned out to be only temporary and did not significantly outlive the ‘Tulip Revolution’.